2011
DOI: 10.1111/j.1365-2753.2011.01656.x
|View full text |Cite
|
Sign up to set email alerts
|

Is discharge knee range of motion a useful and relevant clinical indicator after total knee replacement? Part 2

Abstract: The finding that early knee range predicts longer-term range provides clinical evidence favouring the relevance of discharge knee ROM as a clinical indicator. Although longer-term patient-reported knee pain and function were not directly associated with discharge knee ROM, they were associated with ROM when measured concurrently in the sub-acute phase. No causal effect has been demonstrated, but the findings suggest it may be important for physiotherapists to maximize range in the early and sub-acute periods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 21 publications
4
27
0
4
Order By: Relevance
“…The measurements on postoperative day 2 in this study were not related to long-term outcomes. However, in Australian studies 28,29 in which hospital stays are longer, inpatient ROM measurements of extension performed at discharge on postoperative days 6–8 were related to long-term extension ROM; the same relationship was not observed for flexion.…”
Section: Discussionmentioning
confidence: 85%
“…The measurements on postoperative day 2 in this study were not related to long-term outcomes. However, in Australian studies 28,29 in which hospital stays are longer, inpatient ROM measurements of extension performed at discharge on postoperative days 6–8 were related to long-term extension ROM; the same relationship was not observed for flexion.…”
Section: Discussionmentioning
confidence: 85%
“…Nine published studies [10,13-20] reported the change in mean OKS from baseline to 12 months after primary knee replacement surgery for 13 different groups containing 4,369 patients in total (Table 2). Three studies were RCTs and six were prospective cohort studies.…”
Section: Resultsmentioning
confidence: 99%
“…The risk of selection bias in the recruitment of study participants was considered low in four of the hip replacement studies [6,8,11,12] and eight of the knee replacement studies [13-20] as there was clear evidence that consecutive eligible patients were invited to take part. In two of the hip replacement studies [9,10] and one of the knee replacement studies [10] it was unclear whether this was true.…”
Section: Resultsmentioning
confidence: 99%
“…Naylor et al found that discharge knee ROM may be a useful clinical indicator to evaluate long-term knee ROM restoration prognosis and it may be important for physiotherapists to maximize knee ROM in the early and sub-acute stages after TKA procedures [7]. Restoration of postoperative knee ROM affects both the patient’s health and medical service expenditures.…”
Section: Introductionmentioning
confidence: 99%
“…Patients who have difficulties in regaining the knee ROM must be discovered early and provided with more health services and direct assistance [8]. Of interest to these studies [5,6,7,8], active knee flexion recovery before hospital discharge has revealed a correlation with knee ROM at 12 months postoperation [7,8]. This would suggest that if patients can improve their knee flexion during the early acute inpatient stage, long-term health outcomes and early discharge will be beneficial to the patients.…”
Section: Introductionmentioning
confidence: 99%